Diagnosis of "maladie des feuilles cassantes" or brittle leaf disease of date palms by detection of associated chloroplast encoded double stranded RNAs - Namsi, A.; Marques, Jorge; Fadda, Z.; Takrouni, M. L.; Ben Mahamoud, O.; Zouba, Anis; Daros, José A.; Flores, R.; Bove, J. M.; Durán-Vila, Núria (2017)
The “Maladie des feuilles cassantes” (MFC) or “Brittle leaf disease” of date palms is associated with the accumulation of two populations of small, chloroplast-encoded RNAs. A plasmid vector containing a cDNA with partial sequences of both of these RNA populations was used to synthesize a DIG-labeled bifunctional probe by PCR. The probe has been tested to detect, by molecular hybridization, MFC-associated RNAs from dsRNA-enriched palm leaflet preparations. Leaflet samples from MFC-affected date palm trees consistently gave a positive hybridization signal regardless of the date palm cultivar, severity of symptoms, or geographical location, whereas samples from date palm trees affected by other biotic and abiotic stresses tested negative. The assay is specific for MFC and can be used for early diagnostic purposes.